(untitled) (Nordic Journal of African Studies, 2008)
This paper is an analysis of the Dagaare marker ká aimed at pointing out what the speaker implies when it is used in an utterance. This has been done within the framework of Sperber and Wilson’s communication theory of relevance. Linguistic markers such as pronouns, aspect indicators, mood indicators, hearsay markers and attitudinal particles have been identified as encoding procedural information concerning inference processes relating to utterance interpretation (see Blakemore 1987, 1988, Blass 1990, Wilson and Sperber 1993, Fretheim 2000). Research has shown that these markers encode constraints on the inferential process of utterance interpretation rather than conveying conceptual information. As a result, there is a need for translation strategies that are based on an understanding of the way in which a given marker in a given utterance exploits the inferential comprehension process.